PROBLEMS AND SOLUTIONS IN THE TRANSLATION OF STYLISTIC DEVICES - Atadjanova, Sevara (Журнал иностранных языков и лингвистики, 2023)
In our contribution, we go into the problem of the representation of stylistic devices, their properties, and peculiarities in another, especially a foreign language. It provides some features like translating the device into English and emulating this device in the target language.